Abundant off-axis hydrothermal activity in the 29–30 ridge segment of the Southwest Indian Ridge: evidence from ferromanganese crusts - Yang, Xianhui; Tao, Chunhui; Liao, Shili (Frontiers in Earth Science, 2023)
In the ultra-slow spreading mid-ocean ridge, seafloor hydrothermal ventings mostly occur in the off-axis region. The plume of hydrothermal venting provides Fe, Mn and other metal materials for the growth of ferromanganese crust in the surrounding seamounts, showing unique geochemical characteristics that are different from that of hydrogenetic crust. Based on five samples of ferromanganese crusts, major, trace and rare earth element analysis was carried out to identify their material sources. Combined with the investigation data of water column and seafloor camera photos by deep towed hydrothermal detection system, the potential of hydrothermal activity in the 29–30 ridge segment of the Southwest Indian ridge was evaluated. The results showed that the ferromanganese crust in the study area had significantly higher Fe/Mn value (average 1.9), relatively higher Si and Al contents, and significantly higher Ca/P value (average 9.3),without significant phosphorylation. ferromanganese crust in the study area have significantly lower Co and Ni contents (about 1600 mg/kg on average), and relatively lower Sr, Ba, Pb, Cu, Zr and Mo contents (between 100-1000 mg/kg on average). The contents of W, Th and Te are also relatively low (average content between 10–50 mg/kg); The total rare earth element content of the crust in the study area is relatively low (about 928 mg/kg on average), and the light rare earth is relatively enriched. The standardized rare earth curve of the shale shows a left-leaning pattern as a whole, showing the enrichment of heavy rare earth relative to the shale. The Co content and rare earth element content of the ferromanganese crusts in this area are significantly lower than those of hydrogenetic crusts. The discrimination diagrams of ternary and bivariate material sources reveal that they have mixed hydrothermal and hydrogenetic origins. The three crust samples of S1, S2, and S5 are located within 2 km of the known hydrothermal fields, indicating a correlation between ferromanganese crust and the location of hydrothermal activity. There is no known hydrothermal field near the S3 and S4 stations. Altered rocks and water column turbidity anomalies were found near S3 station, and large areas of altered rocks and suspected hydrothermal biological remains were also found near S4 station, indicating that hydrothermal activity may exist in both areas. In addition to the two new hydrothermal fields identified in this article, the spatial frequency of hydrothermal activity in the study area reaches 15 sites/100 km, which is significantly higher than other well investigated oceanic ridges. Out of the eight hydrothermal fields in the study area, seven are located in the off axis region, mainly because the hydrothermal activity in this area is controlled by high angle and large offset normal faults and one-way detachment faults. This also indicates that the off-axis region of the Southwest Indian Ridge has high potential for hydrothermal activity.